Influence Knowledge Investment, Benefit Investment, Motivation Investment and Minimum Investment Capital Against Investment Interest in Market Capital Sharia On Student in Palopo City - Muh Abdi Imam (Al-Kharaj: Journal of Islamic Economic and Business, 2021)
This study aims to examine the effect of investment knowledge, investment benefits, motivation minimum investment and capital investment on stock investment interest in the capital market sharia. The object of this research is students in Palopo City. The sampling method in this study uses Non Probability Sampling . The data analysis technique used in this research is multiple linear regression analysis. The results of the analysis show that investment knowledge, investment benefits, investment motivation and minimum investment capital have a significant positive effect on investment interest in the Islamic capital market.